-4(-2+5)=6(x-3)

Simple and best practice solution for -4(-2+5)=6(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-2+5)=6(x-3) equation:


-4(-2+5)=6(x-3)

We simplify the equation to the form, which is simple to understand
-4(-2+5)=6(x-3)

Simplifying terms in parentheses
-4*(+3)=6*(x-3)

Reorder the terms in parentheses
+(-12)=6*(x-3)

Remove unnecessary parentheses
-12=+6+*(+x-3+)

Reorder the terms in parentheses
-12=+(+6x-18)

Remove unnecessary parentheses
-12=+6x-18

We move all terms containing x to the left and all other terms to the right.
-6x=-18+12

We simplify left and right side of the equation.
-6x=-6

We divide both sides of the equation by -06 to get x.
x=1

See similar equations:

| 9n-(2n-3)=10 | | 44+55= | | 4y-10+y+54=8y+50-6y | | x-2y=21 | | -(10x+1)+3=-9+6x | | -4x+2=8x-26 | | 5x-7+x=4+5x | | 6x-6=4x+2 | | 20-n=10-2 | | 3x+x+1.5x+180=455 | | (n-1)(5n-2)=0 | | 3x+x+1.5+180=455 | | 5x-12=4x-14 | | -9x^2-48x+15= | | 3x-5=4+2x+8 | | w^2+w=0 | | w=7h+80 | | 5(y-2)=-2(12-9)+y | | 6(4-4)=3(8+3) | | 5x-(6x+(8-(x+1)))=-2x+1 | | 6(4x-4)=3(8x+3) | | m=160-15(6) | | [4x-6]=14 | | 3+16r-2=9r+78-4r | | 5(y-2)=-2(12-9y) | | (-x-1)(-6x+4)=2x*3x | | 3+16r-2=94+78-4r | | 3n+9n=96 | | 4.3-2.1t-2.3=7.6 | | .8(18+x)=7 | | 120=255-15w | | 33+15w=5+6x+9 |

Equations solver categories